Self-repairing wave-absorbing composite material as well as preparation method and application thereof
The composite wave absorbing powder is prepared through plasma ball milling technology and crosslinked with polyurethane prepolymer, which solves the problem of the degradation of traditional wave absorbing composite materials under external force, and achieves improvement of wave absorbing and mechanical properties and rapid self-repair. Suitable for high-frequency electromagnetic wave absorption and high-intensity applications.
Patent Information
- Application Number
- CN202411119120.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-15
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-15
AI Technical Summary
Traditional wave-absorbing composite materials are easily damaged under external forces, resulting in a decrease in wave-absorbing performance and service life, which cannot meet the growing demand for practical applications.
The composite wave absorbing powder is prepared by plasma ball milling technology. Through mechanical vibration and plasma bombardment, the soft magnetic metal particles become thin sheets. Graphene oxide is peeled off to form a nanosheet and the soft magnetic metal surface to form a composite wave absorbing powder, and through The crosslinking reaction of polyurethane prepolymers improves mechanical properties and achieves rapid self-healing of materials.
It significantly improves wave absorption and mechanical properties, and the materials can be quickly self-healed and extend their service life. It is suitable for 5G communications, new energy vehicles, and national defense and military industries.
Smart Images

Figure CN119119716A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of wave-absorbing materials, and in particular to a self-repairable wave-absorbing composite material and a preparation method and application thereof. Background Art
[0002] In recent years, the rapid development of wireless communications has provided great convenience to people's daily lives and communication, but the widespread use of various wireless communication devices and consumer electronic products has also led to serious electromagnetic pollution problems. Electromagnetic pollution not only poses a potential hazard to human health, but also interferes with the stable operation of electronic equipment. For this reason, people are in urgent need of developing absorbing composite materials that can efficiently absorb electromagnetic waves in a specific frequency range. However, the substrates of traditional absorbing composite materials are generally general-purpose rubber or plastic, which are prone to mechanical damage due to external forces during use, or fail due to internal crack expansion caused by material fatigue, which will eventually have a serious impact on the absorbing performance and service life of the material, and cannot fully meet the growing practical application requirements.
[0003] Therefore, it is of great significance to develop an absorbing composite material with excellent absorbing and mechanical properties and capable of rapid self-repair. Summary of the invention
[0004] The purpose of the present invention is to provide a self-repairable wave-absorbing composite material and a preparation method and application thereof.
[0005] The technical solution adopted by the present invention is:
[0006] A self-repairable wave-absorbing composite material includes the following components in percentage by mass:
[0007] Polyurethane matrix: 30% to 80%;
[0008] Composite absorbing powder: 20%~70%.
[0009] Preferably, the composite absorbing powder is made by plasma ball milling graphene oxide and soft magnetic metal powder.
[0010] Further preferably, the composite absorbing powder is made by a preparation method comprising the following steps: ultrasonically dispersing graphene oxide in anhydrous ethanol to prepare a graphene oxide dispersion, then adding the graphene oxide dispersion, soft magnetic metal powder and cemented carbide balls into a ball mill for plasma ball milling, and after the ball milling, taking out the material for vacuum drying to obtain the composite absorbing powder.
[0011] Preferably, the ultrasonic dispersion is carried out under the condition of an ultrasonic power of 100W to 600W, and the ultrasonic dispersion time is 10min to 240min.
[0012] Preferably, the mass ratio of the graphene oxide to the soft magnetic metal powder is 1:10-100.
[0013] Preferably, the soft magnetic metal powder is at least one of carbonyl iron powder, sendustine powder, iron silicon chromium powder and iron nickel powder.
[0014] Preferably, the median particle size (D 50 ) is 1μm~80μm.
[0015] Preferably, the ratio of the total mass of the graphene oxide and the soft magnetic metal powder to the mass of the cemented carbide ball is 1:10-150.
[0016] Preferably, the plasma ball milling is carried out in an argon atmosphere, a nitrogen atmosphere, an oxygen atmosphere or an air atmosphere, the plasma discharge frequency is 5kHz to 12kHz, the atmosphere pressure is 0.01MPa to 0.20MPa, the ball mill speed is 100rpm to 3000rpm, and the ball milling time is 0.5h to 48h.
[0017] Preferably, the vacuum drying is carried out at a temperature of 60° C. to 100° C., and the drying time is 3 h to 48 h.
[0018] A method for preparing the self-repairable wave-absorbing composite material as described above comprises the following steps:
[0019] 1) polytetrahydrofuran diol, isocyanate and catalyst are dispersed in an organic solvent to carry out the first nucleophilic addition reaction, then add oxalyl dihydrazide and diaminodiphenyl disulfide to carry out the second nucleophilic addition reaction, and obtain a polyurethane prepolymer solution;
[0020] 2) The composite absorbing powder is dispersed in a polyurethane prepolymer solution, and then injected into a mold for curing and molding to obtain a self-repairable absorbing composite material.
[0021] Preferably, the molar ratio of the polytetrahydrofuran diol, isocyanate, oxalyl dihydrazide and diaminodiphenyl disulfide is 1:1.4-2.8:0.2-0.8:0.2-0.8.
[0022] Preferably, the number average molecular weight of the polytetrahydrofuran diol in step 1) is 500 to 5000.
[0023] Preferably, the polytetrahydrofuran diol in step 1) is dried and dehydrated at a temperature of 80° C. to 130° C. for 0.5 h to 6 h.
[0024] Preferably, the isocyanate in step 1) is at least one of toluene diisocyanate, isophorone diisocyanate and diphenylmethane diisocyanate.
[0025] Preferably, the catalyst in step 1) is at least one of bis(dimethylaminoethyl) ether, pentamethyldiethylenetriamine, and dibutyltin dilaurate.
[0026] Preferably, the organic solvent in step 1) is at least one of dimethylacetamide, dimethylformamide and tetrahydrofuran.
[0027] Preferably, the diaminodiphenyl disulfide in step 1) is at least one of 2,2'-diaminodiphenyl disulfide and 4,4'-diaminodiphenyl disulfide.
[0028] Preferably, the first nucleophilic addition reaction (nucleophilic addition reaction of isocyanate with the hydroxyl group in polytetrahydrofuran diol) in step 1) is carried out at a temperature of 60° C. to 90° C., and the reaction time is 2 h to 8 h.
[0029] Preferably, the first nucleophilic addition reaction in step 1) is carried out in a nitrogen atmosphere or an argon atmosphere.
[0030] Preferably, the second nucleophilic addition reaction in step 1) (the nucleophilic addition reaction of isocyanate with the amino groups in oxalyl dihydrazide and diaminodiphenyl disulfide) is carried out at a temperature of 40° C. to 60° C., and the reaction time is 6 h to 12 h.
[0031] Preferably, the second nucleophilic addition reaction in step 1) is carried out in a nitrogen atmosphere or an argon atmosphere.
[0032] Preferably, the dispersion method in step 2) is stirring, and the stirring time is 1 hour to 6 hours.
[0033] Preferably, the curing molding in step 2) is carried out at a temperature of 50° C. to 100° C., and the curing molding time is 12 h to 48 h.
[0034] An application of the self-repairable wave-absorbing composite material as described above in the field of 5G communications, new energy vehicles or national defense and military industry.
[0035] Principle of the present invention: The present invention utilizes the shear force and collision force generated by mechanical vibration during plasma ball milling and the thermal effect generated by plasma bombarding powder to quickly transform soft magnetic metal particles into thin sheets, thereby obtaining a greater magnetic permeability and dielectric constant, and enhancing the electromagnetic wave loss capacity of soft magnetic metal materials. At the same time, under the shear force generated by mechanical ball milling, the binding force between graphene oxide sheets is weakened, and the sheets are peeled off to form single-layer or few-layer graphene oxide nanosheets. The graphene oxide nanosheets are complexed with metal ions on the surface of the soft magnetic metal powder, so that the graphene oxide nanosheets can be evenly and tightly coated on the surface of the soft magnetic metal sheet to obtain a composite wave absorbing powder; the graphene oxide on the surface of the composite wave absorbing powder is reduced by plasma to become reduced graphene oxide, which can provide more polarization sites, enhance interface polarization, increase dielectric loss, and enhance the strong ion resonance between the composite wave absorbing powders, thereby obtaining a more excellent wave absorbing performance. In addition, some of the oxygen-containing groups remaining on the surface of reduced graphene oxide can react with free isocyanate groups in polyurethane prepolymers to form crosslinking points, so that the composite absorbing powder can serve as a crosslinkable filler and become the crosslinking center of polyurethane, significantly improving the mechanical properties of the matrix. The absorption of electromagnetic waves by the composite absorbing powder can convert electromagnetic energy into thermal energy, achieve rapid heating of the polymer matrix, and thus realize the rapid self-healing process of the composite absorbing material.
[0036] The beneficial effects of the present invention are as follows: the self-repairable absorbing composite material of the present invention has excellent absorbing performance and mechanical properties, and the material can achieve rapid self-repair, ensuring the stability of the absorbing performance and mechanical properties. The composite material is suitable for 5G communications, new energy vehicles, national defense and military industries and other fields.
[0037] Specifically:
[0038] 1) The present invention utilizes plasma excitation to convert graphene oxide into reduced graphene oxide, thereby enhancing the conductivity of the carbon material, thereby effectively improving the dielectric loss capacity of the composite absorbing powder, and the multiple heterogeneous interfaces formed between the reduced graphene oxide and the soft magnetic metal promote the interface polarization, and the reduced graphene oxide has abundant polarization sites, which enhances the dipole polarization. In addition, the reduced graphene oxide enhances the plasma resonance between the composite absorbing powders, thereby achieving broadband absorption of electromagnetic waves, and significantly enhancing the absorbing performance of the composite powder;
[0039] 2) The oxygen-containing groups on the surface of the composite absorbing powder in the self-repairable absorbing composite material of the present invention can undergo a cross-linking reaction with the polyurethane macromolecules to form covalent bonds, thereby turning the composite absorbing powder into an additional cross-linking center of the composite material, which not only improves the dispersibility of the powder in the polyurethane matrix, but also greatly improves the mechanical properties of the composite material. In addition, the composite absorbing powder can efficiently absorb electromagnetic waves to achieve magnetic-thermal conversion to quickly heat the polymer matrix, thereby accelerating the self-repair speed of the composite material. After repair, the mechanical properties and absorbing properties of the composite material can be restored to their original levels, which helps to extend the service life of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is the SEM image of the microwave-absorbing composite powder of Example 1.
[0041] Figure 2 The minimum reflection loss of the self-repairable absorbing composite materials of Examples 1 to 5 and the absorbing composite materials of Comparative Examples 1 to 2 varies with frequency.
[0042] Figure 3 The stress-strain curves of the self-healing absorbing composite material of Example 1 and the absorbing composite material of Comparative Example 1 before and after self-healing of fracture.
[0043] Figure 4 The minimum reflection loss of the self-repairing absorbing composite material of Example 1 and the absorbing composite material of Comparative Example 1 before and after self-repair of fracture varies with frequency.
[0044] Figure 5 These are optical microscope photos of the fracture position of the self-repairing absorbing composite material of Example 1 before and after self-repair for 10 minutes. DETAILED DESCRIPTION
[0045] The present invention will be further explained and illustrated below in conjunction with specific embodiments.
[0046] Embodiment 1:
[0047] A self-repairable wave-absorbing composite material, which consists of the following components in percentage by mass:
[0048] Polyurethane matrix: 50%;
[0049] Composite absorbing powder (the mass ratio of graphene oxide and carbonyl iron powder is 1:80): 50%.
[0050] The preparation method of the composite absorbing powder is as follows: adding graphene oxide to anhydrous ethanol, ultrasonicating for 20 minutes under an ultrasonic power of 400 W to prepare a graphene oxide dispersion with a concentration of 2.5 mg / mL, then adding the graphene oxide dispersion, carbonyl iron powder (median particle size of 3 μm) and cemented carbide balls to a ball mill, the mass ratio of graphene oxide to carbonyl iron powder is 1:80, the ratio of the total mass of graphene oxide and carbonyl iron powder to the mass of cemented carbide balls is 1:25, and then sealing the ball mill and installing it in a plasma sieve. On the sub-ball mill, evacuate the ball mill and introduce argon until the air pressure in the ball mill is 0.05 MPa, start the vibration control power supply and the plasma discharge control power supply, set the equipment running time to 20 min, the stop time to 20 min, the number of cycles to 30 times, the total ball milling time to 10 h, the ball mill speed to 2000 rpm, the discharge frequency to 11 kHz, start the plasma ball mill for plasma ball milling, take out the material after the ball milling is completed, and vacuum dry it at 80 ° C for 6 h to obtain the composite absorbing powder.
[0051] The preparation method of the self-repairable wave-absorbing composite material is as follows:
[0052] 1) dehydrating polytetrahydrofuran diol (number average molecular weight is 1000) at 120° C. for 30 min, dispersing polytetrahydrofuran diol and isophorone diisocyanate in dimethylacetamide, adding dibutyltin dilaurate accounting for 1.5% of the weight of polytetrahydrofuran diol, stirring and reacting at 80° C. for 3 h under nitrogen protection, cooling to 50° C., adding oxalyl dihydrazide and 2,2'-diaminodiphenyl disulfide and continuing to react for 8 h, wherein the molar ratio of polytetrahydrofuran diol, isophorone diisocyanate, oxalyl dihydrazide and 2,2'-diaminodiphenyl disulfide is 1:2.2:0.5:0.5, and obtaining a polyurethane prepolymer solution;
[0053] 2) The composite absorbing powder and the polyurethane prepolymer solution are mixed in a mass ratio of 1:10, stirred for 4 hours, poured into a polytetrafluoroethylene mold, vacuumed, and reacted at 80° C. for 12 hours to obtain a self-repairable absorbing composite material.
[0054] The scanning electron microscope (SEM) image of the wave absorbing composite powder of this embodiment is as follows: Figure 1 shown.
[0055] Depend on Figure 1 It can be seen that the surface of the absorbing composite powder is rough, the reduced graphene oxide is peeled off into tiny nanosheets, and the reduced graphene oxide nanosheets are tightly combined with the flaky carbonyl iron powder.
[0056] Embodiment 2:
[0057] A self-repairable wave-absorbing composite material, which consists of the following components in percentage by mass:
[0058] Polyurethane matrix: 50%;
[0059] Composite absorbing powder (the mass ratio of graphene oxide and carbonyl iron powder is 1:40): 50%.
[0060] The preparation method of the composite absorbing powder is as follows: adding graphene oxide to anhydrous ethanol, ultrasonicating for 20 minutes under an ultrasonic power of 400 W to prepare a graphene oxide dispersion with a concentration of 5 mg / mL, then adding the graphene oxide dispersion, carbonyl iron powder (median particle size of 3 μm) and cemented carbide balls into a ball mill, the mass ratio of graphene oxide to carbonyl iron powder is 1:40, the total mass of graphene oxide and carbonyl iron powder to the mass of cemented carbide balls is 1:20, and then the ball mill is sealed and installed in a plasma assisted ... On the ball mill, evacuate and introduce argon until the air pressure in the ball mill is 0.05MPa, start the vibration control power supply and plasma discharge control power supply, set the equipment running time to 20min, the stop time to 20min, the number of cycles to 15 times, the total ball milling time to 5h, the ball mill speed to 1500rpm, the discharge frequency to 11kHz, start the plasma ball mill for plasma ball milling, and after the ball milling is completed, take out the material and vacuum dry it at 80℃ for 5h to obtain the composite absorbing powder.
[0061] The preparation method of the self-repairable wave-absorbing composite material is as follows:
[0062] 1) placing polytetrahydrofuran diol (number average molecular weight of 1000) at 100° C. to remove water for 1 hour, then dispersing polytetrahydrofuran diol and isophorone diisocyanate in dimethylacetamide, then adding dibutyltin dilaurate accounting for 1.5% of the weight of polytetrahydrofuran diol, then stirring and reacting at 80° C. for 3 hours under nitrogen protection, then cooling to 50° C., then adding oxalyl dihydrazide and 2,2'-diaminodiphenyl disulfide and continuing to react for 8 hours, the molar ratio of polytetrahydrofuran diol, isophorone diisocyanate, oxalyl dihydrazide, 2,2'-diaminodiphenyl disulfide is 1:2.2:0.4:0.6, to obtain a polyurethane prepolymer solution;
[0063] 2) The composite absorbing powder and the polyurethane prepolymer solution are mixed in a mass ratio of 1:10, stirred for 5 hours, poured into a polytetrafluoroethylene mold, vacuumed, and reacted at 80° C. for 12 hours to obtain a self-repairable absorbing composite material.
[0064] Embodiment 3:
[0065] A self-repairable wave-absorbing composite material, which consists of the following components in percentage by mass:
[0066] Polyurethane matrix: 70%;
[0067] Composite absorbing powder (the mass ratio of graphene oxide and carbonyl iron powder is 1:60): 30%.
[0068] The preparation method of the composite absorbing powder is as follows: adding graphene oxide to anhydrous ethanol, ultrasonicating for 20 minutes under an ultrasonic power of 400 W to prepare a graphene oxide dispersion with a concentration of 3 mg / mL, then adding the graphene oxide dispersion, carbonyl iron powder (median particle size of 3 μm) and cemented carbide balls into a ball mill, the mass ratio of graphene oxide to carbonyl iron powder is 1:60, the total mass of graphene oxide and carbonyl iron powder to the mass of cemented carbide balls is 1:30, and then the ball mill is sealed and installed in a plasma assisted ... On the ball mill, evacuate and introduce nitrogen until the air pressure in the ball mill is 0.05 MPa, start the vibration control power supply and the plasma discharge control power supply, set the equipment running time to 20 min, the stop time to 20 min, the number of cycles to 21 times, the total ball milling time to 7 h, the ball mill speed to 1000 rpm, the discharge frequency to 11 kHz, start the plasma ball mill for plasma ball milling, and after the ball milling is completed, take out the material and vacuum dry it at 70 ° C for 12 h to obtain the composite absorbing powder.
[0069] The preparation method of the self-repairable wave-absorbing composite material is as follows:
[0070] 1) polytetrahydrofuran diol (number average molecular weight is 2000) is placed at 120° C. to remove water for 30 min, polytetrahydrofuran diol and toluene diisocyanate are dispersed in dimethylacetamide, dibutyltin dilaurate accounting for 2% of the weight of polytetrahydrofuran diol is added, and the mixture is stirred and reacted at 60° C. for 6 h under argon protection, and the temperature is then lowered to 50° C., oxalyl dihydrazide and 4,4'-diaminodiphenyl disulfide are added, and the reaction is continued for 10 h, wherein the molar ratio of polytetrahydrofuran diol, toluene diisocyanate, oxalyl dihydrazide and 4,4'-diaminodiphenyl disulfide is 1:2.6:0.7:0.7, to obtain a polyurethane prepolymer solution;
[0071] 2) The composite absorbing powder and the polyurethane prepolymer solution are mixed in a mass ratio of 3:70, stirred for 4 hours, poured into a polytetrafluoroethylene mold, vacuumed, and reacted at 80° C. for 12 hours to obtain a self-repairable absorbing composite material.
[0072] Embodiment 4:
[0073] A self-repairable wave-absorbing composite material, which consists of the following components in percentage by mass:
[0074] Polyurethane matrix: 50%;
[0075] Composite absorbing powder (the mass ratio of graphene oxide and carbonyl iron powder is 1:80): 50%.
[0076] The preparation method of the composite absorbing powder is as follows: adding graphene oxide to anhydrous ethanol, ultrasonicating for 30 minutes under an ultrasonic power of 400 W to prepare a graphene oxide dispersion with a concentration of 2.5 mg / mL, then adding the graphene oxide dispersion, carbonyl iron powder (median particle size of 3 μm) and cemented carbide balls into a ball mill, the mass ratio of graphene oxide to carbonyl iron powder is 1:80, the ratio of the total mass of graphene oxide and carbonyl iron powder to the mass of cemented carbide balls is 1:50, and then the ball mill is sealed and installed in a plasma sieve. On the ball mill, evacuate the ball mill and introduce argon until the air pressure in the ball mill is 0.02 MPa, start the vibration control power supply and the plasma discharge control power supply, set the equipment running time to 30 minutes, the stop time to 30 minutes, the number of cycles to 40 times, the total ball milling time to 20 hours, the ball mill speed to 1500rpm, the discharge frequency to 10kHz, start the plasma ball mill for plasma ball milling, and after the ball milling is completed, take out the material and vacuum dry it at 70°C for 10 hours to obtain a composite absorbing powder.
[0077] The preparation method of the self-repairable wave-absorbing composite material is as follows:
[0078] 1) dehydrating polytetrahydrofuran diol (number average molecular weight of 1000) at 120° C. for 30 min, dispersing polytetrahydrofuran diol and isophorone diisocyanate in dimethylacetamide, adding dibutyltin dilaurate accounting for 2% of the weight of polytetrahydrofuran diol, stirring and reacting at 80° C. for 3 h under nitrogen protection, cooling to 40° C., adding oxalyl dihydrazide and 2,2'-diaminodiphenyl disulfide, and continuing to react for 10 h, wherein the molar ratio of polytetrahydrofuran diol, isophorone diisocyanate, oxalyl dihydrazide and 2,2'-diaminodiphenyl disulfide is 1:2.2:0.5:0.5, to obtain a polyurethane prepolymer solution;
[0079] 2) The composite absorbing powder and the polyurethane prepolymer solution are mixed in a mass ratio of 1:10, stirred for 4 hours, poured into a polytetrafluoroethylene mold, vacuumed, and reacted at 85° C. for 12 hours to obtain a self-repairable absorbing composite material.
[0080] Embodiment 5:
[0081] A self-repairable wave-absorbing composite material, which consists of the following components in percentage by mass:
[0082] Polyurethane matrix: 40%;
[0083] Composite absorbing powder (the mass ratio of graphene oxide and iron-nickel powder is 1:80): 60%.
[0084] The preparation method of the composite absorbing powder is as follows: adding graphene oxide to anhydrous ethanol, ultrasonicating for 20 minutes under an ultrasonic power of 400 W to prepare a graphene oxide dispersion with a concentration of 2.5 mg / mL, then adding the graphene oxide dispersion, iron-nickel powder (median particle size of 20 μm) and cemented carbide balls to a ball mill, the mass ratio of graphene oxide to iron-nickel powder is 1:80, the total mass of graphene oxide and iron-nickel powder to the mass of cemented carbide balls is 1:25, and then the ball mill is sealed and installed in a plasma sieve. On the sub-ball mill, evacuate the ball mill and introduce argon until the air pressure in the ball mill is 0.05 MPa, start the vibration control power supply and the plasma discharge control power supply, set the equipment running time to 20 min, the stop time to 20 min, the number of cycles to 30 times, the total ball milling time to 10 h, the ball mill speed to 2000 rpm, the discharge frequency to 11 kHz, start the plasma ball mill for plasma ball milling, take out the material after the ball milling is completed, and vacuum dry it at 80 ° C for 6 h to obtain the composite absorbing powder.
[0085] The preparation method of the self-repairable wave-absorbing composite material is as follows:
[0086] 1) polytetrahydrofuran diol (number average molecular weight is 3000) is placed at 120° C. and dehydrated for 30 min, polytetrahydrofuran diol and isophorone diisocyanate are dispersed in dimethylacetamide, 1% of bisdimethylaminoethyl ether by weight of polytetrahydrofuran diol is added, stirring reaction is carried out at 70° C. for 6 h under nitrogen protection, the temperature is lowered to 40° C., oxalyl dihydrazide and 2,2'-diaminodiphenyl disulfide are added, and the reaction is continued for 6 h, wherein the molar ratio of polytetrahydrofuran diol, isophorone diisocyanate, oxalyl dihydrazide and 2,2'-diaminodiphenyl disulfide is 1:2.2:0.2:0.8, and a polyurethane prepolymer solution is obtained;
[0087] 2) The composite absorbing powder and the polyurethane prepolymer solution are mixed in a mass ratio of 3:20, stirred for 3 hours, poured into a polytetrafluoroethylene mold, vacuumed, and reacted at 80° C. for 24 hours to obtain a self-repairable absorbing composite material.
[0088] Comparative Example 1:
[0089] A wave-absorbing composite material, which consists of the following components in percentage by mass:
[0090] Polyurethane matrix: 50%;
[0091] Absorbing powder (carbonyl iron powder): 50%.
[0092] The preparation method of the above-mentioned absorbing powder is as follows: add carbonyl iron powder (median particle size is 3 μm) and anhydrous ethanol to a ball mill, the amount ratio of carbonyl iron powder to anhydrous ethanol is 1 g:2.5 mL, and then add cemented carbide balls, the mass ratio of carbonyl iron powder to cemented carbide balls is 1:25, and then seal the ball mill and install it on a vibrating ball mill. After vacuuming, start the vibration control power supply, the total ball milling time is 10 hours, the ball mill speed is 2000 rpm, and after the ball milling is completed, take out the material and place it at 80°C for vacuum drying for 3 hours to obtain the absorbing powder (flake).
[0093] The preparation method of the above-mentioned wave absorbing composite material is as follows:
[0094] 1) polytetrahydrofuran diol (number average molecular weight is 1000) is placed at 120° C. and dehydrated for 30 min, polytetrahydrofuran diol and isophorone diisocyanate are dispersed in dimethylacetamide, 1.5% of dibutyltin dilaurate based on the weight of polytetrahydrofuran diol is added, and the mixture is stirred and reacted at 80° C. for 6 h under argon protection, wherein the molar ratio of polytetrahydrofuran diol to isophorone diisocyanate is 1:1, to obtain a polyurethane prepolymer solution;
[0095] 2) The absorbing powder and the polyurethane prepolymer solution were mixed in a mass ratio of 1:10, stirred for 4 hours, poured into a polytetrafluoroethylene mold, vacuumed, and reacted at 80° C. for 24 hours to obtain an absorbing composite material.
[0096] Comparative Example 2:
[0097] A wave-absorbing composite material, which consists of the following components in percentage by mass:
[0098] Polyurethane matrix: 50%;
[0099] Composite absorbing powder (the mass ratio of graphene oxide and carbonyl iron powder is 1:80): 50%.
[0100] The preparation method of the above-mentioned composite absorbing powder is as follows: graphene oxide is added to anhydrous ethanol, and ultrasonically treated for 20 minutes at an ultrasonic power of 400 W to prepare a graphene oxide dispersion with a concentration of 2.5 mg / mL, and then the graphene oxide dispersion and carbonyl iron powder (median particle size is 3 μm) are mixed and mechanically stirred for 10 minutes. The mass ratio of graphene oxide to carbonyl iron powder is 1:80, and then vacuum dried at 80°C for 6 hours to obtain the composite absorbing powder.
[0101] The preparation method of the above-mentioned wave absorbing composite material is as follows:
[0102] 1) polytetrahydrofuran diol (number average molecular weight is 1000) is placed at 120° C. and dehydrated for 30 min, polytetrahydrofuran diol and isophorone diisocyanate are dispersed in dimethylacetamide, 1.5% of dibutyltin dilaurate based on the weight of polytetrahydrofuran diol is added, and the mixture is stirred and reacted at 80° C. for 6 h under argon protection, wherein the molar ratio of polytetrahydrofuran diol to isophorone diisocyanate is 1:1, to obtain a polyurethane prepolymer solution;
[0103] 2) The composite absorbing powder and the polyurethane prepolymer solution were mixed in a mass ratio of 1:10, stirred for 4 hours, poured into a polytetrafluoroethylene mold, vacuumed, and reacted at 80° C. for 24 hours to obtain an absorbing composite material.
[0104] Performance Test:
[0105] 1) Minimum reflection loss (RL) of the self-repairable absorbing composite materials of Examples 1 to 5 and the absorbing composite materials of Comparative Examples 1 to 2 min ) changes with frequency as shown in the curve Figure 2 shown.
[0106] Depend on Figure 2 It can be seen that compared with the absorbing composite materials of comparative examples 1 to 2, the absorbing performance of the self-healing absorbing composite materials of embodiments 1 to 5 is greatly improved, the minimum reflection loss is significantly reduced, and the effective absorption bandwidth (reflection loss RL<-10dB) is increased.
[0107] 2) The stress-strain curves of the self-repairing absorbing composite material of Example 1 and the absorbing composite material of Comparative Example 1 before and after fracture self-repair are as follows: Figure 3 shown.
[0108] Depend on Figure 3 It can be seen that the self-repairing absorbing composite material of Example 1 has greatly improved tensile strength and self-repairing performance compared with the self-repairing absorbing material of Comparative Example 1.
[0109] 3) The minimum reflection loss of the self-repairing absorbing composite material of Example 1 and the absorbing composite material of Comparative Example 1 before and after self-repair of fracture varies with frequency. Figure 4 shown.
[0110] Depend on Figure 4 It can be seen that the self-healing absorbing composite material of Example 1 can achieve complete restoration of the absorbing performance after self-healing of the fracture, while the absorbing performance of the absorbing composite material of Comparative Example 1 cannot be restored.
[0111] 4) Optical microscope photos of the fracture position of the self-repairing absorbing composite material of Example 1 before and after self-repair for 10 minutes are shown in the figure below: Figure 5 shown.
[0112] Depend on Figure 5It can be seen that the fracture is smooth after self-repairing and is basically completely repaired, indicating that the self-repairing microwave-absorbing composite material of Example 1 has excellent self-repairing performance.
[0113] 5) The test results of the absorbing performance and self-repairing performance of the self-repairable absorbing composite materials of Examples 1 to 5 and the absorbing composite materials of Comparative Examples 1 to 2 are shown in the following table:
[0114] Table 1 Test results of wave absorption performance and self-repairing performance
[0115]
[0116]
[0117] Note:
[0118] Absorption performance: The vector network analyzer was used to test the concentric ring samples with an inner diameter of 3.04 mm and an outer diameter of 7.00 mm. The complex dielectric constant and complex magnetic permeability of the self-repairing absorbing composite material were tested by the coaxial method. The test frequency range was 2 GHz to 18 GHz. According to the transmission line theory, the complex dielectric constant and complex magnetic permeability of the absorber at a given frequency and the thickness of the absorbing material were used to calculate the reflection loss (RL):
[0119] The reflection loss of a single-layer absorber is calculated by formula (1):
[0120] Formula (1): In the formula, Z 0 is the free space impedance, about 377, Z in is the standardized input impedance, calculated as shown in formula (2):
[0121] Formula (2): Z in =(μ r / ε r ) 1 / 2 tanh[j(2πfd / c)(μ r ε r ) 1 / 2 ], where μ r is the free space permeability and the relative permeability of the material, ε r are the free space dielectric constant and the relative dielectric constant of the material, j represents the imaginary part, f is the frequency, d is the sample thickness, and c is the speed of light.
[0122] Self-repairing performance: After the fracture position of the tensile sample is spliced, 1 to 2 drops of ethanol are added to the spliced section, and then heated at 80°C for 10 minutes to evaporate the ethanol, and the mechanical properties and wave absorption properties after repair are tested.
[0123] The mechanical self-healing efficiency is the ratio of the maximum tensile strength after repair to the strength of the undamaged composite material.
[0124] The self-repair efficiency of absorbing performance is the ratio of the overlapping part of the effective absorption bandwidth of the repaired composite material and the absorption bandwidth of the undamaged composite material to the absorption bandwidth of the undamaged composite material at the same thickness.
[0125] From Table 1, we can see that:
[0126] a) The self-repairable absorbing composite materials prepared by plasma ball milling in Examples 1 to 5 have better absorbing performance than the absorbing composite materials prepared by vibration ball milling or ordinary mechanical blending in Comparative Examples 1 to 2. In particular, by adjusting the graphene oxide content, the type of soft magnetic metal, the plasma ball milling conditions and the proportion of the composite absorber in Examples 1 to 5, the reflection loss of the composite material is generally less than -50 dB, and the effective absorption bandwidth is greater than 5 GHz (up to 8.12 GHz), indicating that after the reduction of the graphene oxide, the dielectric loss capacity of the composite powder is greatly improved, and the graphene oxide on the surface of the composite powder provides more polarization sites, which promotes dielectric loss and optimizes impedance matching, thereby obtaining better absorbing performance;
[0127] b) Combination Figure 3 The results show that the tensile strength of the self-repairable absorbing composite material with multiple hydrogen bonds and absorbing powder cross-linking centers in Example 1 can reach up to 28MPa, and the elongation at break can reach up to 900%, which is greatly improved compared with the ordinary polyurethane in Comparative Example 1, indicating that multiple hydrogen bonds enhance the hydrogen bond cross-linking center, and the reduced graphene oxide serves as the covalent bond cross-linking center of the composite material. The two work together to improve the mechanical properties of the composite material. In addition, the combination of disulfide bonds and multiple hydrogen bonds in the self-repairable absorbing composite material of Example 1 gives the composite material excellent self-repairing properties. After 10 minutes of heating repair after tensile fracture, the mechanical repair efficiency can reach 84%, and the absorbing performance repair efficiency can reach 100%.
[0128] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A self-repairable wave-absorbing composite material, characterized in that: The following components are included in mass percentage: Polyurethane matrix: 30% to 80%; Composite absorbing powder: 20% to 70%; The composite wave-absorbing powder is prepared by plasma ball milling graphene oxide and soft magnetic metal powder.
2. The self-repairable wave-absorbing composite material according to claim 1, characterized in that: The mass ratio of the graphene oxide to the soft magnetic metal powder is 1:10-100.
3. The self-repairable wave-absorbing composite material according to claim 1 or 2, characterized in that: The soft magnetic metal powder is at least one of carbonyl iron powder, sendustine powder, iron silicon chromium powder and iron nickel powder.
4. The self-repairable wave-absorbing composite material according to claim 1 or 2, characterized in that: The median particle size of the soft magnetic metal powder is 1 μm to 80 μm.
5. The self-repairable wave-absorbing composite material according to claim 1 or 2, characterized in that: The plasma ball milling is carried out in an argon atmosphere, a nitrogen atmosphere, an oxygen atmosphere or an air atmosphere, the plasma discharge frequency is 5kHz to 12kHz, the atmosphere pressure is 0.01MPa to 0.20MPa, the ball mill speed is 100rpm to 3000rpm, and the ball milling time is 0.5h to 48h.
6. A method for preparing a self-repairable wave-absorbing composite material according to any one of claims 1 to 5, characterized in that: The following steps are involved: 1) polytetrahydrofuran diol, isocyanate and catalyst are dispersed in an organic solvent to carry out the first nucleophilic addition reaction, then add oxalyl dihydrazide and diaminodiphenyl disulfide to carry out the second nucleophilic addition reaction, and obtain a polyurethane prepolymer solution; 2) The composite absorbing powder is dispersed in a polyurethane prepolymer solution, and then injected into a mold for curing and molding to obtain a self-repairable absorbing composite material.
7. The preparation method according to claim 6, characterized in that: The molar ratio of the polytetrahydrofuran diol, isocyanate, oxalyl dihydrazide and diaminodiphenyl disulfide is 1:1.4-2.8:0.2-0.8:0.2-0.
8.
8. The preparation method according to claim 6 or 7, characterized in that: The number average molecular weight of the polytetrahydrofuran diol in step 1) is 500-5000; the isocyanate in step 1) is at least one of toluene diisocyanate, isophorone diisocyanate and diphenylmethane diisocyanate; the diaminodiphenyl disulfide in step 1) is at least one of 2,2'-diaminodiphenyl disulfide and 4,4'-diaminodiphenyl disulfide.
9. The preparation method according to claim 6 or 7, characterized in that: The first nucleophilic addition reaction in step 1) is carried out at a temperature of 60°C to 90°C, and the reaction time is 2h to 8h; the second nucleophilic addition reaction in step 1) is carried out at a temperature of 40°C to 60°C, and the reaction time is 6h to 12h; the curing molding in step 2) is carried out at a temperature of 50°C to 100°C, and the curing molding time is 12h to 48h.
10. An application of the self-repairable wave-absorbing composite material as claimed in any one of claims 1 to 5 in the field of 5G communications, new energy vehicles or national defense and military industry.
Citation Information
Patent Citations
Preparation method of graphene composite wave absorbing material based on 5G communication and application of graphene composite wave absorbing material
CN108865060A
Silicone rubber wave-absorbing composite material and preparation method thereof
CN114133739A
Polyurethane-based wave-absorbing composite material and preparation method thereof
CN115073908A
Bionic environment adaptability self-repairing coating as well as preparation method and application thereof
CN115216219A
Graphene composite material and manufacturing method for the same
JP2022179441A
Cited By
Self-repairing broadband wave-absorbing composite material as well as preparation method and application thereof
CN120206943A
Self-repairing wave-absorbing composite material as well as preparation method and application thereof
CN120590785A
Self-repairing wave-absorbing composite material, preparation method and application thereof
CN120590785B
